Republic of Kosovo : Request for Stand-By Arrangement: Staff Report; Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2012)
This staff report discusses the Republic of Kosovo's request for a Stand-By Arrangement. Kosovo is in the final stages of transition to full self-governance in economic and financial affairs. Kosovo's economy has remained largely shielded from turbulence in the euro area, owing to limited integration into cross-border financial markets and a small export base. Real GDP growth in 2011 is estimated at 5 percent, driven principally by domestic demand, in particular investment. Inflation has been moderated to 3.5 percent, after a spike to double-digit figures in early 2011 triggered by higher prices for imported foodstuffs.